Pediatric basilar skull fractures from multi-level falls: A systematic review and retrospective analysis. (November 2022) - Barba, Patrick; Stramiello, Joshua A.; Nardone, Zachary; Walsh-Blackmore, Seth; Nation, Javan; Ignacio, Romeo; Magit, Anthony
Abstract: Objective: Multi-level fall (MLF) accounts for 26.5%–37.7% of traumatic pediatric basilar skull fractures (BSFs). There is a dearth of information concerning recommendations for work-up, diagnosis, treatment, and otolaryngological follow-up of pediatric basilar skull fractures secondary to MLFs. Through a systematic literature review and retrospective review of an institution's trauma experience, we sought to identify clinical findings among pediatric MLF patients that indicate the need for otolaryngological follow-up. Methods: A two-researcher team following the PRISMA guidelines performed a systematic literature review. PubMed, Web of Science, and EBSCO databases were searched August 16th, 2020 and again on November 20th, 2021 for English language articles published after 1980 using search terms Pediatric AND (fall OR "multi level fall" OR "fall from height") AND ("basilar fracture" OR "basilar skull fracture" OR "skull base fracture" OR "skull fracture"). Simultaneously, an institutional trauma database and retrospective chart review was performed for all patients under age 18 who presented with a MLF to a pediatric tertiary care center between 2007 and 2018. Results: 168 publications were identified and 13 articles reporting pediatric basilar skull fracture data and MLF as a mechanism of injury were selected for review. MLF is the most common etiology of BSF, accounting for 26.5–37.7% of pediatric BSFs. In the retrospective review, there were 180 cases of BSF from MLF in the study period (4.2%). BSF and fall height were significantly associated (p < 0.001), as well as presence of a CSF leak and fall height (p = 0.02), intracranial hemorrhage (ICH) (p = 0.047), and BSF fracture type (p < 0.001). However, when stratified by age, these associations were only present in the younger group. Of those with non-temporal bone BSFs (n = 71), children with hemotympanum (n = 7) were approximately 18 times more likely (RR 18.3, 95% CI 1.89 to 177.02) than children without hemotympanum (n = 64) to have hearing loss at presentation (28.6% vs. 1.6% of patients). Conclusions: MLF is the most common cause of pediatric basilar skull fractures. However, there is limited information on the appropriate work-up or otolaryngologic follow-up for this mechanism of injury. Our retrospective review suggests fall height is predictive for BSF, ICH, and CSF leak in younger children. Also, children with non-temporal bone BSFs and hemotympanum may represent a significant population requiring otolaryngology follow-up.